Students' Thinking Style in Analyzing Physics Concept Through the Kinametic Graphics - Saminan, Saminan; Muliana, Endah; Wahyuni, Agus (Jurnal Ilmiah Peuradeun, 2019)
Students' thinking style is influential in learning outcomes, but teachers have not yet focused on the teaching and learning process, resulting in students having difficulties in receiving the material, especially in the study of analyzing physical concepts through graphs on the concept of kinematics. Therefore, knowing the student's thinking style especially for the physics teacher is a very important effort to achieve teaching success. This study aims to determine the students' thinking style in analyzing physical concepts through graphs on kinematics concepts. The approach used in this study is a qualitative approach with a type of descriptive research. Subjects in this study were students of class X Mipa1 and X Mipa2. Data collection instruments in this study were questionnaire, observation and documentation. The questionnaire used was in the form of a closed questionnaire adapted from the Quantum Learning book written by Bobbi DePorter and Mike Hernacki, The results of this study indicated that the concrete sequential thinking style (S1) was 27 %, abstract sequential thinking style (S2) was 14%, random abstract (A1) was 34%, concrete random thinking style (A2) was 25%.